The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1345/aph.1l496
|View full text |Cite
|
Sign up to set email alerts
|

Adherence: Comparison of Methods to Assess Medication Adherence and Classify Nonadherence

Abstract: All measures provided similar estimates of overall adherence, although refill and electronic measures were in highest agreement. In selection of a measure, practitioners should consider population and disease characteristics, since measurement agreement could be influenced by these and other factors. The commonly used, clinically based cut-point of 80% had a reasonable balance between sensitivity and specificity in studies of adherence in patients with heart failure or hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
219
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(228 citation statements)
references
References 27 publications
3
219
0
6
Order By: Relevance
“…Patients may acquire the tablets but not take them and this measure does not provide us with information with respect to the time of taking the medication or reasons for non-adherence. However, it showed relatively good agreement with electronic pill container, especially in depressed patients (Hansen et al 2009). Moreover, this measure allowed us to collect information without the patient being aware that he or she was being assessed even when the patients did not keep their evaluation appointments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Patients may acquire the tablets but not take them and this measure does not provide us with information with respect to the time of taking the medication or reasons for non-adherence. However, it showed relatively good agreement with electronic pill container, especially in depressed patients (Hansen et al 2009). Moreover, this measure allowed us to collect information without the patient being aware that he or she was being assessed even when the patients did not keep their evaluation appointments.…”
Section: Discussionmentioning
confidence: 93%
“…Non-adherence was defined as refilling <80% of the prescribed doses; a definition that has a reasonable balance between sensitivity and specificity (Hansen et al 2009) or having a treatment gap >1 month (Peterson et al 2007). …”
Section: Measurementsmentioning
confidence: 99%
“…First, this study was conducted at a single institution, and the results may not be generalizable. Second, although refill adherence is considered a valid and objective measure which correlates highly with pill count and electronic monitoring, 31,44,45 it is a surrogate outcome and does not directly capture daily medication taking behavior, which was a target of the illustrated medication schedule intervention. Third, refill adherence may be underestimated if patients use other pharmacies from which data are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacy refill records were used to measure IST adherence since they are an objective measure of the quantity of medication dispensed, are highly correlated with electronic medication monitoring, and have been used successfully in other medication adherence studies, demonstrating significant associations with health outcomes (34)(35)(36)(37). Additionally, research has indicated that RTRs who get their IST refills filled appropriately are more likely to have desired IST serum concentrations, indicating that RTRs took their IST (12).…”
Section: Outcome Measuresmentioning
confidence: 99%